2019
DOI: 10.1186/s12864-019-5794-y
|View full text |Cite
|
Sign up to set email alerts
|

Events of alternative splicing in head and neck cancer via RNA sequencing – an update

Abstract: Background Alternative splicing (AS) is a regulatory mechanism used to create many forms of mature messengers RNAs (mRNAs) from the same gene. Sequencing of RNA (RNA-Seq) is an advanced technology, which has been utilized by different studies to find AS mechanisms in head and neck cancer (HNC). Hitherto, there is no available review that could inform us of the major findings from these studies. Hence, we aim to perform a systematic literature search following PRISMA guidelines to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Therefore, a comprehensive understanding of the AS model is critical to the future treatment strategy for cancer. The emergence of RNA-Seq technology and the cancer genome database has become a new tool for studying AS events in pancreatic adenocarcinoma, helping to identify new therapeutic and molecular targets for pancreatic adenocarcinoma [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a comprehensive understanding of the AS model is critical to the future treatment strategy for cancer. The emergence of RNA-Seq technology and the cancer genome database has become a new tool for studying AS events in pancreatic adenocarcinoma, helping to identify new therapeutic and molecular targets for pancreatic adenocarcinoma [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that RPS9 dysregulation was involved in tumorigenesis, such as pancreatic cancer, head, and neck cancer (such as head and neck squamous cell carcinoma) and so on [13][14][15] . Moreover, evidence indicated suggested that RPS9 knockdown suppressed proliferation through P53 independent mechanisms in U2OS cells, impaired 18S rRNA production in glioma cells by P53 and accelerated cell death in cervical carcinoma HeLa cells [16] .…”
Section: Ivyspringmentioning
confidence: 99%
“…Prior literature suggests a role of alternative splicing in HNSCC. Multiple studies have attempted to systematically identify alternative splicing events associated with HNSCC prognosis. For example, re-clustering TCGA HNSCC RNA-Seq data based on alternative splicing events resulted in four clusters that highly resemble the four molecular subtypes of HNSCC . Additionally, a previous phosphoproteomics and proteomics study comparing normal versus HNSCC cell lines identified RNA splicing as one of the most changed cellular processes in this cancer type .…”
Section: Introductionmentioning
confidence: 99%